Thermoelectric properties of phase separated Ti substituted Zr0.75Hf0.25NiSn0.985Sb0.015 half-Heuslers - Akram, Rizwan; Yan, Yonggao; Hussain, Mozaffar; She, Xiaoyu; Tang, Xinfeng (Progress in natural science, 2020)
Sb is a very effective dopant for ZrNiSn based half-Heusler alloys. The effect of Ti substitution on Zr0.75Hf0.25NiSn0.985Sb0.015 half-Heusler (HH) semiconductor alloys has been investigated to explore the structural modifications and composition variation. TixHf0.25 Zr0.75-xNiSn0.985Sb0.015 (x = 0, 0.15, 0.30, 0.45) alloys were synthesized by induction melting. A set of samples was also annealed for comparative studies. The samples were then sintered using plasma activated sintering (PAS) technique. XRD results confirmed the existence of ZrNiSn type HH compounds. Backscattered electron (BSE) images showed phase separations in the samples. Ti substitution improved the carrier concentration and electrical conductivity of the alloys. Moreover, thermal conductivity was also significantly reduced due to the enhanced phonon scattering. Consequently, a ZT value of 1.11 at 873 K was obtained for 30% Ti substituted (annealed) sample. [Display omitted] •Effect of Ti substitution on Zr0.75Hf0.25NiSn0.985Sb0.015 half-Heusler (HH) semiconductor alloys is investigated.•Backscattered electron (BSE) images showed phase separations in the samples.•Carrier concentration and electrical conductivity of the alloys was enhanced while thermal conductivity was reduced.•A ZT value of 1.11 at 873 K was obtained for 30% Ti substituted (annealed) sample.